2017
DOI: 10.3390/f8120503
|View full text |Cite
|
Sign up to set email alerts
|

Value Retention, Service Life, Use Intensity and Long-Term Productivity of Wood Chippers as Obtained from Contractor Records

Abstract: Acknowledging the absence of up-to-date empirical data on the value retention, service life and annual use of chipping machinery, in 2017 the authors surveyed the records kept by 50 contractors offering biomass chipping services. The machine fleet and operations in this survey could be taken as representative for most of Europe, where the biomass sector is well established and is facing further expansion. Data collection included the whole chipping unit, comprised of chipper, carrier and loader. Manually-fed u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…The operational cost depends on all the incurred expenses when the chipper unit is actually operating. Conversely, the capital cost depends on the initial investment, the economic service life of the chipper unit, and the interest rate charged on borrowed capital; it is incurred whether or not the machine is working (Nurminen et al 2009;Ackerman et al 2014;Spinelli et al 2017). The investment risk exists because it is uncertain that the cost of the investment will be recovered and a profit gained (Virlics 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The operational cost depends on all the incurred expenses when the chipper unit is actually operating. Conversely, the capital cost depends on the initial investment, the economic service life of the chipper unit, and the interest rate charged on borrowed capital; it is incurred whether or not the machine is working (Nurminen et al 2009;Ackerman et al 2014;Spinelli et al 2017). The investment risk exists because it is uncertain that the cost of the investment will be recovered and a profit gained (Virlics 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Chippers do a very heavy job and are subject to high wear (Spinelli et al 2017). For this reason, regular maintenance is essential to avoid failures and achieve a long service life.…”
Section: Maintenancementioning
confidence: 99%
“…The basic ones include: a cylindrical chipper [1], a drum chipper [2], a disc chipper [3], a hammer chipper [4], or a spiral chipper [5]. Chippers for the industrial production of biomass, with high capacity (indicated in scientific publications on the power range from 130 kW to 900 kW [6]), have the wood chips outlet system based on the forced motion of the cutting mechanism [2,3,[7][8][9][10][11]. Chippers used on urban areas for tree care in parks, gardens, and by-road surfaces are low power machines (Figure 1).…”
Section: Introductionmentioning
confidence: 99%